Comparison of front crawl swimming drag between elite and non-elite swimmers using pressure measurement and motion analysis - Ichikawa, H.; Miwa, T.; Takeda, T.; Takagi, H.; Tsubakimoto, S. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: The hydrodynamic force exerted on a swimmer is changing from moment to moment during swimming. It is important to understand the dynamics of swimming to discuss the swimming technique and performance. The purpose of the study is to suggest a methodology to quantify the drag force, which was changing during front crawl swimming, and to compare the swimming drag between elite and non-elite swimmers. METHODS: The subjects were a well-trained male competitive swimmer (49.6 sec/100mFr.) and a male triathlete (82.0 sec/100mFr.). The trial was the front crawl swimming using arm only in a swim-mill, which was set the flowing velocity to 1.3 m/s. The estimation of the drag force was based on the equation of motion, that is"ma = Fp + Fd", along with swimming direction. The twelve small pressure sensors were attached on the subject`s both hands in order to measure the pressure distribution and to calculate the hydrodynamic force exerted on the hands. The attitude of both hands during underwater phase was calculated by the videography and 3D-DLT method. The propulsive force Fp was calculated as a component along with swimming direction of the hydrodynamic force on the hands, assuming that the swimmers produced the propulsive force by the hands only. The swimming acceleration a in the inertial term of the equation was calculated from the position of the umbilical part, as an alternative point of the center of gravity, which was recorded using a high speed camera with 250 fps. All measurements in the experiment were synchronized. RESULTS: The inertial term, the propulsive force and the drag force during 5 seconds were obtained in each trial. The mean drag forces were 21.3 N in elite swimmer and 50.3 N in non-elite, respectively. The maximum drag forces were 90.3 N in elite and 189.4 N in non-elite. The non-elite swimmer kept producing propulsive force with high stroke frequency. The mean propulsive force of the non-elite swimmer was higher than that of the elite swimmer (25.5 N in elite and 51.4 N in non-elite). DISCUSSION: The non-elite swimmer had to keep producing the propulsive force in order to maintain the swimming velocity, because of the larger drag force and de-acceleration. The smaller drag force in the elite swimmer would make it easy to keep the swimming velocity. It was suggested that our methodology to quantify the drag force during front crawl swimming would be useful to understand the dynamics and to discuss the performance of swimming.